2022
DOI: 10.1155/2022/1713213
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter jejuni from Slaughter Age Broiler Chickens: Genetic Characterization, Virulence, and Antimicrobial Resistance Genes

Abstract: Campylobacter jejuni is a major cause of food-borne human gastroenteritis worldwide and is designated as a high priority antimicrobial-resistant pathogen by the World Health Organization (WHO). In this study, a total of 26 C. jejuni isolates from broiler chickens were screened for the presence of virulence and antimicrobial resistance genes by PCR. As a result, the study detected 11/26 (42.3%), 9/26 (34.6%), 8/26 (30.8%), 7/26 (26.9%), 6/26 (23.1%), and 6/26 (23.1%) of cdtC, pldA, cdtB, cdtA, cadF, and ciaB vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 68 publications
0
3
1
Order By: Relevance
“…Our results were nearly like to [39,40,13 and 41] which recorded the high percentage of the cdtA gene (85%) in chicken C. jejuni isolates. but our results were in Contrary to [42] that found a low occurrence of cdtA gene in chickens with a percentage of 26.9%. In this study, the total detection of the virB gene was detected in different percentages as it appeared as 43% total percentage and its percentages were 58.3%, and 33.3% in chickens and pigeons respectively.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results were nearly like to [39,40,13 and 41] which recorded the high percentage of the cdtA gene (85%) in chicken C. jejuni isolates. but our results were in Contrary to [42] that found a low occurrence of cdtA gene in chickens with a percentage of 26.9%. In this study, the total detection of the virB gene was detected in different percentages as it appeared as 43% total percentage and its percentages were 58.3%, and 33.3% in chickens and pigeons respectively.…”
Section: Discussioncontrasting
confidence: 99%
“…When considering the ARGs detected in the studies included in this meta-analysis, it was observed that multidrug resistance was potentially due to efflux pump systems. Multidrug efflux systems are the most common mechanism of bacterial resistance to antimicrobial drugs [ 53 , 54 ]. Efflux pumps have been linked as one of the mechanism responsible to increase antibiotic resistance in bacteria biofilm structures as they allow faster diffusion rate of antibiotics [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In South African broilers, in 26 C. jejuni isolates, the highest antimicrobial resistance was detected to nalidixic acid (96.1%), tetracycline (80.7%) and erythromycin (84.6%), while resistance to ciprofloxacin was present in only 19.2%. The prevalence of the catI, catII, catIII, catIV, floR, ermB, tetO, tetA, mcr-4 and ampC genes were present in 84.2%, 78.9%, 52.6%, 10.5%, 52.6%, 73.7%, 68.4%, 47.4%, 42.1% and 10.5% of the tested isolates [66]. Similarly, antimicrobial resistance genes from 132 Campylobacter (C. jejuni and C. coli) poultry isolates were favourably prevalent, ranging from 80 to 100% for the cmeB, tetO and bla OXA-61 genes among all tested isolates, while the aphA-3 gene was not detected in any of the strains.…”
Section: Recent Updates On Antibiotic Resistance Among Campylobacter ...mentioning
confidence: 97%
“…Class I integrons have been found in Campylobacter, but neither class II nor class III integrons have been detected in these species [97]. However, 92.3% of C. jejuni isolates displayed the presence of Class I integrons, whereas 65.4% of the tested isolates harboured Class II integrons [66].…”
Section: Virulence and Antibiotic Resistance Of Campylobacter Spp Pou...mentioning
confidence: 97%